The Effect of Pre-Extraction Preparation on Antioxidant Compounds of Sauropus androgynus (L.) Merr. Leaves Extracts - Hikmawanti, Ni Putu Ermi; Fatmawati, Sofia; Arifin, Zainal; Cahyaningrum, Niken; Arif Fauzan, Muhammad (UI Scholars Hub, 2021)
Sauropus androgynus (L.) Merr. (Phyllanthaceae) is a green vegetable. It is rich in natural antioxidant compounds such as phenolics and flavonoids. The pre-extraction preparation can affect the results of extracting compounds from natural materials. This study aims to determine the effect of pre-extraction procedures, including sample form (fresh/dried), drying process (oven-drying/indirect sunlight-drying/air-drying), and particle size (ground/powdered) on total phenolic and flavonoid levels of ethanolic extracts of S. androgynus leaves and their antioxidant activity against DPPH radicals. S. androgynus leaves were extracted using the cold maceration method. The total phenolic and flavonoid contents of the extract were determined by the colorimetric method using a UV-Vis spectrophotometer. Antioxidant activity was measured based on the ability of the extracts to reduce DPPH free radicals. The results showed that the pre-extraction preparation influenced the antioxidant components obtained in S. androgynus leaves. According to sample form, fresh leaves contained a higher phenolics and flavonoids (33.66 mg GAE/g and 11.61 mg QE/g, respectively) than dried leaves. Whereas according to particle size, powdered dried leaves have higher phenolics and flavonoids content (45.12 mg GAE/g and 12.54 mg QE/g, respectively) than ground dried leaves. The leaves drying method that produced the highest phenolic content was oven-drying (47.08 mg GAE/g), while the one with the highest flavonoid content was air-drying (8.87 mg QE/g). All extracts had IC50 values against DPPH radicals around 85.71-93.91 ppm. Pre-extraction preparation in optimum condition makes the extraction process more efficient and effective in obtaining the target compounds with antioxidant activities.